Essentials for parathyroid imaging and intervention: what radiologists need to know - Choi, Hye Jeong; Kim, Ji-hoon (Ultrasonography (Seoul, Korea), 2025)
The parathyroid glands play a key role in maintaining calcium–phosphate homeostasis by secreting parathyroid hormone (PTH). Hyperparathyroidism, characterized by the inappropriate overproduction of PTH, is classified as primary, secondary, or tertiary according to its pathophysiology. Although diagnosis is principally biochemical, imaging is essential for accurately localizing hyperfunctioning glands. Precise localization allows for focused minimally invasive surgery, reduces the risk of persistent or recurrent disease, and avoids unnecessary bilateral neck exploration. Current techniques include high-resolution ultrasonography, 99mTc-sestamibi scintigraphy with single-photon emission computed tomography/computed tomography (CT), four-dimensional CT, magnetic resonance imaging, and positron emission tomography/CT with tracers such as 18F-fluorocholine. Parathyroidectomy remains the mainstay of treatment; however, recent advances in thermal ablation have expanded treatment options for patients unsuitable for surgery.